Rosette-forming epithelioid osteosarcoma in the rib: a rare case of location and morphology - Sun-Ju Oh (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
The rib is an unusual location for osteosarcoma and is reported in only 2% of all cases. The major histological variants of osteosarcoma are osteoblastic, chondroblastic, and fibroblastic, with a few rare variants including one epithelioid type. This report describes a 44-year-old male with an osteolytic mass in the right seventh rib. Histological examination revealed osteosarcoma with unique features of epithelioid appearance and rosette structures. To the best of our knowledge, this is the first reported case of a rosette-forming osteosarcoma of the rib that showed epithelioid morphology. Despite successful surgery, the patient's prognosis was poor because this malignancy had an unusual location within the axial skeleton and was a rare histological variant.